Process Improvement for Environmental Impact Mitigation in an Industrial Laundry - Montoya, Walter (2020)
DOI: https://doi.org/10.26439/ing.ind2020.n038.4816 Nowadays it is not enough to reduce costs or increase productivity; it is also necessary to focus process improvements on mitigating the environmental impact. Forthis reason, the current situation of the WALU industrial laundry was analyzed using the environmental risk identification matrix as diagnostic methodology to propose improvements that mitigate and eliminate the environmental impact, changing the business model to a sustainable one.